2022
DOI: 10.3389/fimmu.2022.947712
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Mutation Status and Immune Landscape for Squamous Cell Carcinomas at Different Anatomical sites

Abstract: ObjectiveIt has been controversial whether tumor mutation burden (TMB) affects the prognosis and the efficacy of immunotherapy in different tumor types. We provided a comprehensive analysis of mutation status and immune landscape of squamous cell carcinomas (SCCs) from four sites in order to investigate the relationship of TMB with prognosis and immune cell infiltration in different SCCs.MethodsThe transcriptome profiles and somatic mutation data of SCCs downloaded from the Cancer Genome Atlas (the Cancer Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
4
8
0
Order By: Relevance
“…Univariate and multivariate Cox analyses were also employed to determine if that risk score was an independent prognostic factor ( Figure 5 D). Recent studies have demonstrated that high tumor mutation burden (TMB) was associated with poor prognosis in HNSCC [ 7 ]. Considering the prognostic effects of TMB, we further examined the potential relationship between TMB and our risk model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Univariate and multivariate Cox analyses were also employed to determine if that risk score was an independent prognostic factor ( Figure 5 D). Recent studies have demonstrated that high tumor mutation burden (TMB) was associated with poor prognosis in HNSCC [ 7 ]. Considering the prognostic effects of TMB, we further examined the potential relationship between TMB and our risk model.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, predictive biomarkers based on the intrinsic characteristics of the tumor, such as TMB and gene mutation, were also introduced in our study [ 28 ]. TMB is characterized by the number of tumor gene variants and has been widely used for immunotherapy assessment [ 7 , 29 ]. Recent studies observed that the tumor suppressor gene TP53 mutation was associated with high TMB [ 30 ], and it might predict prognostic outcomes for HNSCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of in ltrated immune cells was estimated using SSGSEA method. CIBERSORT (https://cibersort.stanford.edu/index.php) is used to characterize cell composition based on gene expression pro les of complex tissues [19]. CIBERSORT was combined with LM22 to estimate the proportion of 22 immune cell phenotypes among different groups.…”
Section: Correlation Analysis Of Immune Characteristics Of M 6 a Regu...mentioning
confidence: 99%
“…Checkpoint inhibitors are known to be significantly more effective in tumors with higher mutational burden, including lung cancers and skin cancers such as melanoma [ 14 , 15 ]. The efficacy of immunotherapy in lung cancer patients based on their smoking status thus calls for detailed examination [ 16 ], since tobacco smoke is known to induce DNA damage and mutations in several oncogenes and tumor suppressor genes [ 17 , 18 ], resulting in higher mutational burden [ 19 ]; this has been validated in multiple tumor types, including squamous cell carcinomas of the lung, and head and neck [ 20 , 21 ]. It has been suggested that the prevalence of cancer-specific mutated peptides, which are generated as a result of somatic mutations caused by smoking, might increase the prevalence of neo-antigen-specific T cells, enhancing the response to checkpoint blockade [ 22 ].…”
Section: Smoking and Immunotherapy Efficacymentioning
confidence: 99%